Rehabilitation at Home with Interactive Technology Following Total Knee Arthroplasty - Gordon, Adam M.; Sharma, Rajan; Mont, Michael A. (The Journal of Knee Surgery, 2025)
Smartphone applications and wearable devices have shown promising outcomes to augment in-person postoperative total knee arthroplasty rehabilitation. Advantages of these technologies include patient-specific, real-time feedback, and motivation that can be integrated into newer rehabilitation protocols. These technologies can be utilized in the home setting with patient-directed therapy. This brief narrative review discusses the current utilization of smartphone applications and sensors for the postoperative rehabilitation period following total knee arthroplasty. This review will discuss how they are utilized for home-based rehabilitation and the outcomes of patients who utilize them. This review specifically focuses on recovery outcomes such as adherence/satisfaction, functional improvement, and gait patterns. Outcomes are primarily descriptive, with p-values noted where appropriate. This review highlights the growing evidence supporting the use of smartphone applications and wearable sensors as valuable tools in the rehabilitation process following total knee arthroplasty. Both technologies have been shown to enhance patient adherence, improve functional outcomes, mitigate pain, and provide valuable data for healthcare providers and patients. Importantly, the integration of these technologies, such as the combination of smartphone apps with wearable devices, can help improve patient outcomes when utilized in a home-based rehabilitation setting. Smartphone applications and wearable devices offer enhancements in postoperative rehabilitation following total knee arthroplasty. Despite being in their infancy, randomized trials have validated their effectiveness and utility in this context. Improved adherence to postoperative care plans emerged as a recurrent findings.
Keywords: total knee arthroplasty; functional outcomes; sensors; smartphone applications; rehabilitation